2021
DOI: 10.1111/ijfs.15228
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsions: formation, stability and an account of dietary polyphenol encapsulation

Abstract: Summary To enhance nutraceutical performance, vehicle systems are required to promote the usage of food supplements, which have shown an increasingly growing demand. These food supplements such as dietary polyphenols are nutritious constituents but with varying solubility, sensitivity to oxygen, light, temperature, or adverse effects encountered during processing, making their incorporation difficult in foods. Additionally, these are bound to the food matrix so tightly, that they are not available to be taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The benefits of nanoemulsions include small particle size and high dispersion. These properties allow them to defy gravity through Brownian motion, preventing precipitation during storage and ensuring the homogeneity of the system ( Marhamati et al, 2021 ; Siraj et al, 2021 ). Nanoemulsions, on the other hand, are thermodynamically unstable, and the smaller the droplet size, the higher the interfacial energy, the more likely it is that Ostwald ripening will occur, and the simpler it will be to transfer fluid from small to large droplets, which ultimately causes the emulsion to coarsen ( McClements, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of nanoemulsions include small particle size and high dispersion. These properties allow them to defy gravity through Brownian motion, preventing precipitation during storage and ensuring the homogeneity of the system ( Marhamati et al, 2021 ; Siraj et al, 2021 ). Nanoemulsions, on the other hand, are thermodynamically unstable, and the smaller the droplet size, the higher the interfacial energy, the more likely it is that Ostwald ripening will occur, and the simpler it will be to transfer fluid from small to large droplets, which ultimately causes the emulsion to coarsen ( McClements, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the constructed polyphenol delivery system shows good performance in vitro and in vivo models and improves the stability, bioavailability, and targeting of dietary polyphenols to a certain extent. 30,31 Even so, because the human structure is more precise and complex than that of animals, there are still some challenges for the polyphenol delivery system to achieve clinical application:…”
Section: ■ Intestinal Microenvironmentmentioning
confidence: 99%
“…At the same time, emulsification systems (liposomes, nano lotion, double lotion, and Pickering lotion) and nano/particle systems (protein-based, carbohydrate-based, and double-polymer-based) can deliver polyphenols and other bioactive substances to the body and tissues. Currently, the constructed polyphenol delivery system shows good performance in vitro and in vivo models and improves the stability, bioavailability, and targeting of dietary polyphenols to a certain extent. , Even so, because the human structure is more precise and complex than that of animals, there are still some challenges for the polyphenol delivery system to achieve clinical application: Safety issues: strictly control the quality and structure of nanomaterials, and choose carefully to avoid toxicity and side effects in vivo . Modification methods: chemical, physical, and biological modification, covalent and non-covalent combination, etc., may affect the structure, properties, and activity of polyphenols. Application performance of packaging materials: the metabolic process and release characteristics of the matrix delivering polyphenols in vivo need to be clear, and whether it can achieve the sustained-release effect. Differences in complex properties: what are the differences between the complex’s biological activity and physiological mechanism after the delivery matrix is combined with polyphenols and unpackaged polyphenols. Model differences: cell and animal models cannot accurately reflect the human body’s metabolic process of polyphenol complexes, and the models have individual differences. …”
Section: Bioavailability and Stability Of Dietary Polyphenolsmentioning
confidence: 99%
“…In recent years, curcumin has gained more and more attention since an increasing number of studies focused on the extraction and purification of curcumin, its biological activity and pharmacological effects (Shakoor et al, 2021;Sun et al, 2021). Studies have found that curcumin is not only an effective oxygen free radical scavenger, but also a credible bioactive for chronic diseases (Duan et al, 2021;Moon et al, 2021;Siraj et al, 2021). In addition, the study in animal models found that curcumin also has a certain effect in the prevention of Alzheimer's disease (Maiti et al, 2019;Sedighi et al, 2018;Hwang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%